Responsive Web-Based E-Voting Information System: Sistem Informasi E-Voting Berbasis Web Responsive - Cahyo, Habby Nur; Suryawinata, Mohammad (Indonesian Journal of Innovation Studies, 2022)
Technological advancement has growth rapidly impacted to bring great changes to humans. It is included for voting. By utilizing the advancement and growth of the technology, voting is conducted computer technology in the term of electronic voting or generally referred to as e-voting. The problem currently being confronted by the chairman’s election is the COVID-19 pandemic, which makes it impossible to hold a direct election. This research uses qualitative research methods through system development method in carrying out the the SDLC (System Development Lift Cycle) method as it has gone through several e-voting system development processes such as design, analysis, prototype, and implementation. In building this e-voting, the application design uses the PHP programming language, HTML tags, Mysql database as a database server, Web Hosting. The development of this e-voting application is web-based online. Thus, the e-voting applications can be accessed online. Based on the test results, it can be concluded that the application of online e-voting can be implemented to the election of the chairman of RT.01 RW.03 Kludan Village. It can be proved through the application testing to 10 random voters by filling out a questionnaire and getting the results of application acceptance of 83% which is encompassed as very good category.